Kesadaran Metakognitif Siswa dalam Penerapan Kurikulum Merdeka Pada Mata Pelajaran Bahasa Indonesia di SMAN 8 Padang - Fariq, M; Ramadhanti, Dina; Mana, Lira Hayu Afdetis (Universitas Swadaya Gunung Jati, 2024)
Metacognition is a central part of controlling the thinking process. Students who have good metacognitive skills are assumed to be able to control their own thinking processes so that they become independent learners. Metacognitive awareness plays an important role in the implementation of learning. Therefore, this study aims to describe students' metacognitive awareness in the implementation of the independent curriculum for Indonesian language subjects at SMA Negeri 8 Padang. This type of research is quantitative with a descriptive method. Data collection was carried out by giving questionnaires to 100 samples and interviews. Data analysis was carried out in two ways, namely descriptive analysis for questionnaire data and content analysis for interview data. The results of this study indicate that students' metacognitive awareness at SMA Negeri 8 Padang in the implementation of the independent curriculum for Indonesian language subjects is classified as good with a percentage of 79.10%. Regarding metacognitive knowledge, students have very good awareness with a rate of 82.47%. In terms of metacognitive strategies, students have good awareness with a percentage of 77.36%. Students already have awareness of metacognitive knowledge and need encouragement in efforts to increase awareness of metacognitive strategies. Teachers also need to motivate students and always carry out activities that encourage increased metacognitive awareness in students.